Paradigm change in Pentateuchal research - Armgardt, Matthias; Kilchör, Benjamin; Zehnder, Markus (Zeitschrift für altorientalische und biblische Rechtsgeschichte, 2019)
This volume collects papers originally presented at an international meeting held in March 2017. They compellingly demonstrate the necessity for a "Paradigm Change in Pentateuchal Research" from various angles. It is by now generally recognised that the old paradigm, classically formulated in Wellhausens "Prolegomena zu einer Geschichte Israels", can no longer command a dominant position in the reconstruction of the genesis and structure of the Pentateuch. While the studies collected in this volume do not suggest that there is only one specific direction for the search of a new paradigm, they make clear that an important element for the furthering of the discussion is the use of empirical methods, in contradistinction to a dominance of subjective criteria and approaches developed in circumstances that are foreign to the cultural world of the ancient Near East. The authors of the studies represent diverse backgrounds not only in terms of geography, but especially in terms of professional specialization: Besides Biblical Studies, also the fields of Assyriology, Legal History, and Linguistics are represented. Some of the studies address methodological questions in an explicit and detailed way, while others are more focused on the analysis of specific texts. A majority of the studies convincingly demonstrate that most of the Pentateuch can be solidly rooted in the pre-exilic period. --